COFFEE CONSUMPTION MAY DECREASE THE SERUM CREATININE AND PLASMA MALONDIALDEHYDE LEVELS IN RATS WITH HYPERURICEMIA INDUCED BY A HIGH PURINE DIET - Hilmi Ardian Sudiarto; Rahma Yuantari; Dwi Nur Ahsani (Universitas Syiah Kuala, 2021)
The aim of this research was to determine the effect of coffee on creatinine and plasma malondialdehyde (MDA) level in rats fed on high purine diet. A total of 24 male Wistar rats divided into 4 groups of 6 rats each. Beef broth were given to 3 groups (K1, P1, P2) for thirty days. Beef broth administration were followed by giving coffee (caffeinated= P1 or by a decaffeinated= P2, 144 mg/200 g BW). Serum creatinine levels and plasma MDA were examined periodically on day 0, 15, and 30. Data were analyzed by multivariate analysis of variance or MANOVA test (CI= 95%, P0.05). Coffee administration (caffeinated and decaffeinated) may decrease the serum creatinine (day-30, K1= 3.17+ 0.69; P1= 1.63+0.11; P2= 1.14+0.08) and MDA levels (day-30, K1= 9.8+0.28; P1= 5.80+0.55, P2= 3.87+3.26) after 30 days of treatment (P= 0.000 for creatinine and MDA levels in K1, P1, P2 groups). A lower serum creatinine and MDA levels can be found in decaffeinated coffee grup. Coffee consumption for 30 days (especially decaffeinated) may decrease serum creatinine and plasma MDA in rat induced by a high purine diet.